DelEnsembleElec: Computing Ensemble-Averaged Electrostatics Using DelPhi (Communications in Computational Physics, 2013)
A new VMD plugin that interfaces with DelPhi to provide ensemble-averaged electrostatic calculations using the Poisson-Boltzmann equation is presented. Thegeneral theory and context of this approach are discussed, and examples of the plugininterface and calculations are presented. This new tool is applied to systems of currentbiological interest, obtaining the ensemble-averaged electrostatic properties of the twomajor influenza virus glycoproteins, hemagglutinin and neuraminidase, from explicitly solvated all-atom molecular dynamics trajectories. The differences between theensemble-averaged electrostatics and those obtained from a single structure are examined in detail for these examples, revealing how the plugin can be a powerful tool infacilitating the modeling of electrostatic interactions in biological systems.